RE-DESIGN KEMASAN PRODUK KACANG ATOM GDR DI NAGARI PANYALAIAN, KECAMATAN X KOTO, KABUPATEN TANAH DATAR - ILHAM SYUKRI, Dr. Budiwirman, M.Pd. San Ahdi, M.Sn., M.Ds. (DEKAVE : Jurnal Desain Komunikasi Visual, 2017)
One of the pillars of national economic development is the expansion of small and medium industries. With the presence of a home industry that aims to promote the increase of the National Peanut Enterprises Atom